Political religious extremism and its impact on social security: A study at Gaza Strip, Palestine / Mona J.M Abumarzouq - Mona J.M , Abumarzouq (2020)
This study, named 'political religious extremism and its impact on societal security: A Study at Gaza Strip, Palestine ', approaches its types, causes, manifestations, effects, attitude of interpreters and how university students in Gaza Strip perceive its reality and impact. Moreover, the role of lecturers in approaching it, and detecting of statistical differences in how the sample’s individuals realize reality of the phenomenon, attributed to the variables: (gender - university - governorate). The researcher follows the descriptive, applied, analytical approach, by extrapolating texts related to the topic comprehensively, extracting a base from contemporary interpretations, an applied study that combines interviews and questionnaire, describing the results, analyzing and interpreting them, and explaining ways of prevention and treatment. The most important results are that religious extremism is a product of religious, political, social, economic or educational conditions that created its types; the most influential factor is the boldness and misunderstanding of God’s rulings, and the influence of deviant beliefs that are contrary to the moderate approach. Its impacts are also clear, but the misleading focus of the media on Sunni groups as an example of extremism, and its serious consequences from the emergence of misguided ideas contrary to the nation culture, and contradictory groups in the principles and beliefs. The attitudes of interpreters are parallel in that the basic principle is establishing of Al-Sharia in all fields and relations between Muslims and others, and refusing to acknowledge its validity obliges the person the features of immorality and disbelief and injustice, if scholars do not persevere in the opposition and avoid the Sharia, they would betray what they believed in, the students' awareness of problem has an average degree). The lecturers 'role in approaching it is limited by the lack of vii methodology, and the problem is spread in a varying degree, and there are no statistical differences at (α ≥.0.0) between the averages of students' awareness of the problem due to the gender variable in addition to statistical differences due to the variable of residence and university for the Rafah region and Al-Quds University, the most important recommendations is to activate the role of technology to explain the danger of the problem and spread of moderation and advancement of the culture of society in line with the religious teachings, conduct training courses for lecturers and speakers to approach in thoughtful ways with extremism, and adopt planning for societal political security.